AN ANALYSIS CODE SWTICHING BY LANGUAGE TEACHERS WITH STUDENTS OF MIX PROFICIENCY LEVELS OF ENGLISH AT A SUB SECONDARY SCHOOL - Norkhairi Ahmad; Syafini Ismail (Universitas Duta Bangsa Surakarta, 2022)
Code switching is a linguistic phenomenon within bilingual and multilingual settings around the world. For a multiracial country like Malaysia, it is crucial to examine the linguistic realities of the multilingual communities where the presence of code switching is the hallmark. A crucial area where code switching happens but not thoroughly studied is within the educational at school between teachers and students. This study set outs to explore the nature of code-switching that occur between language teachers and students in the school context. A qualitative case-study method via purposive sampling of seven English language teachers at a sub urban secondary school was adopted for this research endeavor. Rich data was elicited via written interviews comprising five key questions were distributed to all the English language teachers as respondents. The teachers responded in full to all questions and the data were prepared, qualitatively analyzed and verified. A summary of the responses was generated and presented as key findings for the study. There were general consensus among the English teachers that code switching is present as part of their repertoire of tools and strategies to ease and facilitate the learning process when situations demand for it. Code switching as a tool serves useful communication and pedagogic functions for the teachers to utilize strategically and not indiscriminately. It is used only when necessaryÂ particularly when teaching groups of students with low language proficiency. The findings from this study are significant as it shed light on the realities of teaching and learning languages. The contrastive view that code switching is not permissible for being an obstacle to learning a target language needs to be reassessed and the view that it a taboo in language teaching and learning must also be dispelled.